2017
DOI: 10.3389/fmicb.2017.02460
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pathogenic Vibrio parahaemolyticus from the Chesapeake Bay, Maryland

Abstract: Vibrio parahaemolyticus is the leading cause of bacterial gastroenteritis associated with seafood consumption in the United States. Here we investigated the presence of virulence factors and genetic diversity of V. parahaemolyticus isolated from water, oyster, and sediment samples from the Chesapeake Bay, Maryland. Of more than 2,350 presumptive Vibrio collected, more than half were confirmed through PCR as V. parahaemolyticus, with 10 encoding both tdh and trh and 6 encoding only trh. Potentially pathogenic V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…Though considered a "gold standard", it is only recently that PFGE has been extensively employed for subtyping environmental strains of V. parahaemolyticus [8,42,43]. The PFGE pattern of the 15 isolates of this study showed considerable diversity and the new serovars having pandemic attributes were not related to the pandemic O3:K6 isolate.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Though considered a "gold standard", it is only recently that PFGE has been extensively employed for subtyping environmental strains of V. parahaemolyticus [8,42,43]. The PFGE pattern of the 15 isolates of this study showed considerable diversity and the new serovars having pandemic attributes were not related to the pandemic O3:K6 isolate.…”
Section: Discussionmentioning
confidence: 65%
“…Though a majority of clinical V. parahaemolyticus generally carry tdh and/or trh, only a small proportion of environmental isolates have been found to harbour the hemolysin genes [6][7][8]. T3SS1 that produce cytotoxicity is present in all V. parahaemolyticus isolates irrespective of their source.…”
Section: Introductionmentioning
confidence: 99%
“…By the early 1970s, Vibrio parahaemolyticus was recognized as a cause of diarrheal disease worldwide, most commonly in Asia and the United States. Vibrio parahaemolyticus associated with sea foods is one of the leading agent for food borne illness in China and across the world (Chen et al, 2017;Yang et al, 2017). Although cooking destroys this organism, sea snails are sometime eaten raw and will lead to infections associated with V. parahaemolyticus.…”
Section: Introductionmentioning
confidence: 99%
“…Vibrio parahaemolyticus, a highly reported pathogenic bacteria of aquatic environment, belongs to vibrionaceae family has emerged as the leading cause of seafood-associated gastroenteritis and a significant hazard for global aquaculture (Tang et al, 2014, Ghenem et al, 2017, Chen et al, 2017, Letchumanan et al, 2014. The overgrowing population, with increased purchasing power worldwide, has enhanced the demand for and export potential of seafood, resulting in the steady expansion of the aquaculture industry (Rico et al, 2012).…”
Section: Introductionmentioning
confidence: 99%